A CRÍTICA SOCIAL DO DITO DE JEREMIAS CONTRA O REI JEOAQUIM: Uma análise exegética de Jeremias 22,13-19 (609-598 a.C) - Ripoli, Fernando (2014)
This exegetical study aims to demonstrate the social criticism of Jeremiah against King Jehoiakim, the main source of social criticism Jr 22,13-19. To this end, we leave the analysis of literary, historical and religious context of social criticism of Jeremiah, then make the exegetical analysis of the proposed text, through which we will focus, among the various content, social justice embedded in the passage. Understanding a text arises within a social environment, will highlight based on social criticism, the violent practices of King Jehoiakim in his reign against the wronged workers, the poor and needy in the society of Judah Finally, demonstrating the historical issues the prophet Jeremiah in his international experiences among the existing empires, and the oppressive system of King Jehoiakim against the disadvantaged of society Judah.